Relationship between carbon dioxide gradient/arteriovenous oxygen gradient index and lactate in septic shock secondary to pneumonia - Trujillo-Ulloa, Washington Alfonso (2020)
Objective: To determine the relationship between carbon dioxide gradient/arteriovenous oxygen gradient index and lactate in patients with pneumonia complicated by septic shock in areas delivering care for critically ill or injured patients of the Hospital III EsSalud Chimbote between 2018 and 2019. Materials and methods: A quantitative, observational, correlational, longitudinal trend study. The study population consisted of patients with pneumonia complicated by septic shock who had carbon dioxide gradient/arteriovenous oxygen gradient index and lactate readings. Results: Ninety (90) patients with pneumonia complicated by septic shock participated in the research. The present study showed a robust relationship between gas gradient index and serum lactate when monitoring patients at baseline, 3 hours, 6 hours and 12 hours. Conclusions: There is a relationship between carbon dioxide gradient/arteriovenous oxygen gradient index (> 1.4) and serum lactate levels in patients with septic shock secondary to pneumonia.